The Impact of Internal Governance and Psychological Safety on Employee Performance in Private Universities: The Mediating Role of Organizational Communication - Yuda Supriatna; Amarul Amarul; Ariz Taufiq (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Internal governance and psychological safety are key factors influencing employee performance in private universities in Indonesia. Internal governance ensures efficient and transparent operations aligned with institutional goals, whereas psychological safety allows employees to express ideas and take risks without fear of negative consequences. Organizational communication mediates the relationship between these factors and employee performance. This study aimed to assess the impact of internal governance and psychological safety on employee performance in private universities in Banten, with organizational communication as an intervening variable. This study explores how these elements contribute to performance through effective communication. A quantitative approach was employed with a sample of 50 respondents from private universities in Banten. Data were collected via structured surveys, and SmartPLS 4.0 software was used to analyze the relationships between internal governance, psychological safety, organizational communication, and employee performance. This study found that internal governance positively influenced organizational communication, which significantly enhanced employee performance. Psychological safety also contributes to organizational communication but has a minimal direct impact on performance. Organizational communication plays a crucial mediating role in linking governance, safety, and performance. These findings emphasize the importance of strengthening internal governance, fostering psychological safety, and improving organizational communication to optimize employee performance in private universities. By focusing on these factors, universities can create a more supportive environment that enhances employee engagement and effectiveness of the faculty.